2016
DOI: 10.1371/journal.pone.0159518
|View full text |Cite
|
Sign up to set email alerts
|

High Hospitalization Rates in Survivors of Childhood Cancer: A Longitudinal Follow-Up Study Using Medical Record Linkage

Abstract: Hospitalization rates over time of childhood cancer survivors (CCS) provide insight into the burden of unfavorable health conditions on CCS and health care resources. The objective of our study was to examine trends in hospitalizations of CCS and risk factors in comparison with the general population. We performed a medical record linkage study of a cohort of 1564 ≥five-year CCS with national registers. We obtained a random sample of the general population matched on year of birth, gender and calendar year per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 44 publications
4
29
0
Order By: Relevance
“…We, moreover, found that most CCS contacted their PCP for benign conditions of the skin and that for skin conditions, CCS contacted their PCP 1.2 times as often as controls. The literature on benign skin conditions in long‐term CCS is scarce, and skin conditions were not known to elevate hospitalization rates in CCS . Our results suggest the importance of investigating the course of disease of different benign skin conditions as compared with the general population, and to determine whether different treatment might be beneficial for CCS.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…We, moreover, found that most CCS contacted their PCP for benign conditions of the skin and that for skin conditions, CCS contacted their PCP 1.2 times as often as controls. The literature on benign skin conditions in long‐term CCS is scarce, and skin conditions were not known to elevate hospitalization rates in CCS . Our results suggest the importance of investigating the course of disease of different benign skin conditions as compared with the general population, and to determine whether different treatment might be beneficial for CCS.…”
Section: Discussionmentioning
confidence: 86%
“…Subsequent neoplasms and endocrine disorders were also among the most important causes for hospitalization. 17 Hematological conditions did not lead to elevated hospitalization rates in CCS. 17 However, in this study, CCS were over three times more likely to require health care for hematological conditions than controls.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies based upon hospital admissions have shown that the risk of hospitalisation for respiratory conditions are increased for CCS compared to the general population . However, only one of these studies has looked at specific types of admissions for respiratory diseases …”
Section: Introductionmentioning
confidence: 99%